Character education in the digital era: An analytical review of hate speech on social media platforms - Suryanto, Edy; Mukhibun, Akhmad; Rahmawati, Anggita; Putri, Fransiska Heavany Devina Kusuma; Junear, Klara Alma Grace; Rohmah, Ronaa Dzakiyyah (Humanities Horizon, 2025)
The development of digital technology has changed the pattern of social interaction, especially among Generation Z who grew up alongside social media. With the existence of social media providing convenience in communication and self-expression, therefore new challenges arise in character building, one of which is the rise of hate speech. This study aims to identify the forms of hate speech committed by Generation Z on social media and examine the challenges of character education in dealing with it. The method used is netnography with a text analysis approach to social media posts and comments that contain hateful content. The results showed that common forms of hate speech include insults, defamation, defamation, unpleasant actions, provocation, incitement, and spreading fake news. This phenomenon shows that low digital literacy and lack of understanding of ethics in social media are serious problems. Other challenges faced in character education include exposure to inappropriate digital content, excessive dependence on technology, and the lack of supervisory role from parents and educators. Therefore, a solution that requires synergy from various parties such as teachers, families, government, and digital platforms to strengthen character education through increasing digital literacy, habituation of postal communication, and social media ethics.